Between Secularity and Post-Secularity: Critical Appraisal of Charles Taylor's Account - Žalec, Bojan (Bogoslovni vestnik (Tiskana izd.), 2019)
The article deals with Charles Taylor's account of the secular age. In the first part, the main constituents of Taylor's narrative account are presented: the central concepts, distinctions, definition of the subject, the aims etc. The author pays special attention to the notions of secularity, secular age, religion, and transcendence. In the second part, Taylor's genealogy of the secular age is outlined and comparatively placed in the context of other main relative forms of genealogical account. Because our age is an age of authenticity, a special section is devoted to it. The final section presents some reproaches to Taylor and evaluates their strength and the value of Taylor's contribution. Besides, some speculative »forecasts« about secularity and post-secularity in Europe, the USA, and at the global scale are presented (by reference to Taylor's account). The author concludes that despite some (serious and cogent) reproaches and second thoughts about Taylor's account, it is doubtless one of the major achievements in the area that manifests features of a paradigmatic work. It helps us a lot to understand the condition of religion not only in the past and today, but also gives us directions and guidelines, conceptual and methodological tools, and ideas to more clearly discern the forms and condition of religion in the future.